2019
DOI: 10.1016/j.ijppaw.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of parasites and pseudoparasites in wolves (Canis lupus) across continents: A comparison among Yellowstone (USA), Abruzzo (IT) and Mercantour (FR) national parks

Abstract: Little is known about the impact of infectious diseases on large carnivores. We investigated factors structuring the helminth and protozoan infections of wolves (Canis lupus) by using coprological analyses. Faecal samples (n = 342) were analysed from 11 wolf packs belonging to three different geographical and ecological settings in Italy (Abruzzo, Lazio e Molise National Park, PNALM: 4 packs, 88 samples), in France (Mercantour National Park, PNM: 4 packs, 68 samples) and in the U.S.A. (Yellowstone National Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 68 publications
3
16
0
Order By: Relevance
“…For each Taeniidae, the frequency or prevalence detected are reported if provided in the respective literature sources. Crenosoma vulpis larvae, Toxocara canis and coccidian oocysts, as previously detected in wolves both from Italy and other countries in Europe [2,17,18,23,30,44].…”
Section: Toxocara Canissupporting
confidence: 54%
See 2 more Smart Citations
“…For each Taeniidae, the frequency or prevalence detected are reported if provided in the respective literature sources. Crenosoma vulpis larvae, Toxocara canis and coccidian oocysts, as previously detected in wolves both from Italy and other countries in Europe [2,17,18,23,30,44].…”
Section: Toxocara Canissupporting
confidence: 54%
“…In this study, microscopic examination also demonstrated the occurrence of Capillaria spp., Ancylostomatidae eggs, Crenosoma vulpis larvae , Toxocara canis and coccidian oocysts, as previously detected in wolves both from Italy and other countries in Europe [ 2 , 17 , 18 , 23 , 30 , 44 ].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Ongoing studies of wolf-parasite associations are particularly important as emerging findings from Europe and North America have revealed new infections and spatial changes in parasitism of wolves (Beck et al, 2017;Ćirović et al, 2015;Hermosilla et al, 2017;Molnar et al, 2015Molnar et al, , 2019Pavlović et al, 2018) as well as in other canids (Fuehrer et al, 2016). Given that canids host several zoonotic parasites, changing host-parasite relationships could have major implications for both ecosystem and public health (Cerda et al, 2018;Tasić-Otašević et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our aim with this comparative study, which includes different ecosystems, sampling periods, and parasitological methods, was to investigate associations between predator-prey relationships and parasite communities. Here, we combined results from three studies (Bryan et al, 2012;Molnar et al, 2019;Stronen et al, 2011) and compiled associated data on population metrics, such as wolf density and dietary diversity (Tables 1 and 2). The three studies include data from six wolf populations on two continents.…”
Section: Introductionmentioning
confidence: 99%